MODEL PEMBERDAYAAN MASYARAKAT DI KAMPUNG TEMATIK MULYAHARJA BOGOR BERBASIS PENDAMPINGAN PERGURUAN TINGGI - Parantika, Asep; Wibowo, FX Setiyo (Jurnal Analisis Pariwisata; Vol 20 No 01 (2020): Jurnal Analisis Pariwisata (2020), 2021)
The study have aims to find out the solving method for problems in Kampung Tematik Mulyaharja and to design society empowerment model based on university assistance. This study is qualitative and field research which use action research method. Having four respondent namely chief of village office (Lurah), secretary of village office (Seklur), manager of thematic village, chief of mature farmer group (Kelompok Tani Dewasa) and chief of youth group organization (karangtaruna). This study hold since February, 2018 until September, 2019. The result is a solving problem method as fishbone chart which is completed by explanation of problem, solving and progress report each aspect, namely institutional aspect, Vision aspect, activity aspect, amnities aspect, accesbility aspect and entrpreneuship aspect. Furthermore, the method designed for society empowerment is having shape of circle which contained of ten steps which connected each other and continues. The steps are 1) choose the candidate of partner village; 2) decide the category of tourism village; 3) do the MoU; 4) decide the program targets; 5) identify the potentials of tourism village; 6) manage the empowerment programs; 7) implement the assistance programs; 8) direct the college resources; 9) promote the outcome of program; and 10) evaluate the program. Keywords : empowerment model, based on assistance, university, tourism village.